INTERPRETASI PAJAK DAN PERSEPSI WAJIB PAJAK SERTA IMPLIKASINYA TERHADAP PEMBAYARAN PAJAK (Studi Kasus Pada UMKM Kuliner di Dinoyo, Kota Malang) - Nur Aini; Nur Hidayati; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is to analyze the tax interpretation andtaxpayer perceptions and their implications on the payment of culinary UMKMtax in Dinoyo, Malang city. The method used is quantitative method. Thepopulation of this research is culinary UMKM located in Dinoyo, Malang city.The sample in this study were 93 respondents.This research used primary data which are collected by questionnairedistribution. To examine the relationship between tax interpellation andtaxpayer's perception and the implication to tax payment, multiple linearregression test is used through SPSS ver 14 software.The results showed that tax interpretation and perception of taxpayerssimultaneously have a significant effect on tax payments. And from the test resultspartially, obtained the result that the tax interpretation variable shows a positivenumber and has a significant influence on tax payments. While the taxpayerperception variable also shows a positive number and has a significant influenceon tax paymentsKeywords: Tax Interpretation, Taxpayer Perception, Tax Payment, UMKM